Principles and theories of learning and sustainable development - Bunyadi, Weerasak; Arunno, Soonthorn; Surisaeng, Chakthorn (JOURNAL MAHA CHULA TANI MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY, 2022)
The study of principles and theories of learning and sustainable development is the basis for developing the concept of sustainable development. Know the meaning of sustainable development made aware of the United Nations sustainable development approach to have the benefit of the United Nations sustainable development. The human and human environment in the development that will lead to sustainability. It is not possible to develop any part, causing the need to change the development model, make use of resources. Investment direction of technology development and new institutional change as the main goal is With regard to justice and there is balance and equality to promote sustainability and enable current and future generations to use resources to know the value of the natural environment. So for Thailand the country has developed according to the trend of global development into a truly concrete development era. By defining a policy of managing the country to develop economic prosperity to the public thoroughly. And to define this sustainable development as a national agenda to lead to a level of living that will lead to sustainability by encouraging changes in consumption patterns and production, including moral values, ethics, culture, which is the foundation of behavior related to various parts many parts, including economy, society, politics, development and environment.